From Clientelistic Governance to Embedded Autonomy: A Transformative Patron-client Approach in Pangkep Regency Development - Muchlis, ‎; Ibrahim, Muh. Akmal (KnE Social Sciences, 2025)
This study analyzes the opportunities for transformation of patron-client relations from clientelistic governance to embedded autonomy in the context of Pangkep Regency development. Using a qualitative approach through in-depth interviews, Musrenbang observations, and document analysis, the study identifies patron-client typologies in the maritime, mining, and island sectors and their manifestations in regional development administration. The results of the study indicate that the pattern of development project allocation and decision-making is strongly influenced by patronage networks, but has the potential to be transformed through the formalization of social networks. The institutionalization of the punggawa-sawi system in coastal management and the integration of informal figures in participatory planning create a hybrid governance structure that combines the strength of traditional relations with modern administrative principles. The developed embedded autonomy model results in increased effectiveness of policy implementation and more substantive community participation. This study contributes to the theoretical discourse on the transformation of social structures in regional development and offers a practical approach to utilizing local social capital in strengthening governance capacity without ignoring traditional wisdom.